Identifying Predictors of Career Calling in University Students: A Systematic Literature Review - Mulyana, Olievia Prabandini; Izzati, Umi Anugerah; Mulyana, Phonny Aditiawan; Nur'aini, Nadja Alfin; Rahma, Earlene Tania; Afifah, Ainun Nur Aini (Indonesia Approach Education, 2024)
Career calling plays a crucial role in shaping an individual’s career journey. It provides essential direction for students in their learning process and helps establish clear career goals. related to learning and a clear direction for career goals. This study aims to explore the whole and the predictor variables that can affect students' career calling. This study uses a systematic literature review combined with bibliometric analysis method by searching reputable journals through databases: ScienceDirect, Springer, SAGE Journals, Frontiers, MDPI, Wiley Online Library, and Taylor & Francis. Based on a series of systematic literature review methods in reputable journals, 11 relevant articles were obtained. The study results show that 13 factors can affect students' career calling. In conclusion, these factors are categorized into three parts: individual attributes, psychological factors, and environmental factors.